Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products and Services: Phase 1: Pacific (Tonga) - Taufatofua, Pita (Technical Centre for Agricultural and Rural Cooperation, 2005)
CTA commissioned this study in Tonga as part of an assessment of agricultural information needs in ACP States. The study covers a country profile, information needs analysis and capacity building needs, and identifies areas for possible collaboration...